Effect of adiponectin on bovine granulosa cell steroidogenesis, oocyte maturation and embryo development - Coyral-Castel Stéphanie; Ramé Christelle; Perreau Christine; Guignot Florence; Uzbekova Svetlana; Maillard Virginie; Dupont Joëlle (BMC, 2010)
Abstract Background Adiponectin is an adipokine, mainly produced by adipose tissue. It regulates several reproductive processes. The protein expression of the adiponectin system (adiponectin, its receptors, AdipoR1 and AdipoR2 and the APPL1 adaptor) in bovine ovary and its role on ovarian cells and embryo, remain however to be determined. Methods Here, we identified the adiponectin system in bovine ovarian cells and embryo using RT-PCR, immunoblotting and immunohistochemistry. Furthermore, we investigated in vitro the effects of recombinant human adiponectin (10 micro g/mL) on proliferation of granulosa cells (GC) measured by [3H] thymidine incorporation, progesterone and estradiol secretions measured by radioimmunoassay in the culture medium of GC, nuclear oocyte maturation and early embryo development. Results We show that the mRNAs and proteins for the adiponectin system are present in bovine ovary (small and large follicles and corpus luteum) and embryo. Adiponectin, AdipoR1 and AdipoR2 were more precisely localized in oocyte, GC and theca cells. Adiponectin increased IGF-1 10(-8) M-induced GC proliferation (P < 0.01) but not basal or insulin 10(-8) M-induced proliferation. Additionally, adiponectin decreased insulin 10(-8) M-induced, but not basal or IGF-1 10(-8) M-induced secretions of progesterone (P < 0.01) and estradiol (P < 0.05) by GC. This decrease in insulin-induced steroidogenesis was associated with a decrease in ERK1/2 MAPK phosphorylation in GC pre-treated with adiponectin. Finally, addition of adiponectin during in vitro maturation affected neither the percentage of oocyte in metaphase-II nor 48-h cleavage and blastocyst day 8 rates. Conclusions In bovine species, adiponectin decreased insulin-induced steroidogenesis and increased IGF-1-induced proliferation of cultured GC through a potential involvement of ERK1/2 MAPK pathway, whereas it did not modify oocyte maturation and embryo development in vitro.